Omental cyst: a case report and review of the literature - Keenan J. Robbins; Ryan M. Antiel; Baddr A. Shakhsheer (SpringerOpen, 2021)
Abstract Background Omental cysts are rare, predominantly occur in children, and often initially present with symptoms masquerading as other more common intra-abdominal pathologies. In this case report, we present the case of a child with an omental cyst that originated from the lesser sac. Due to the location of this cyst, resection presented unique technical challenges that have not been described in existing literature. Case presentation A 4-year-old male patient presented with symptoms initially concerning for appendicitis. Ultrasound showed a normal appendix but a large volume of complex intraperitoneal fluid. Computed tomography subsequently demonstrated a large cystic structure spanning from the stomach to the bladder. The patient was taken to the operating room where a large omental cyst was found to originate from the lesser sac. The resection was difficult due to the thin wall of the cyst and the intimate association of the superior-most aspect of the cyst with the tail of the pancreas, but was ultimately successful. Conclusions Omental cysts are rarely suspected before detection on abdominal imaging. Surgical resection is the treatment of choice, and complete resection can result in a recurrence-free postoperative course. Laparoscopic resection has been reported, but laparotomy is reasonable when a minimally invasive approach may not allow for a safe resection without rupture of the cyst. Anatomical characteristics of the cyst, as demonstrated in our case, can present challenges in the treatment of this otherwise benign entity.